The Role of the Business Leader in the Incorporation and Affirmation of the Corporate Social Responsibility in the Business Organization - Stefanova, Marina; Mihaleva, Yoana (Research Papers, 2020)
The study aims to validate the role of the Business leader’s personal traits and activities to incorporate the values ??and practices of corporate social responsibility (CSR) in one Bulgarian company. The authors review the scientific literature in order to outline the interrelations between the personality of the business leader and the company CSR practices; conducting an empirical study among the employees of a Bulgarian large enterprise and testing the Sustainable Leadership Model, developed by the Institute for Sustainable Leadership at the University of Cambridge, UK.The authors apply a "single case study" approach, ie. research in a large Bulgarian company with well-established CSR policies and practices. The field work was conducted at three levels: qualitative research through a personal interview with the organization’s business leader; quantitative research among representatives of senior and middle management; and another one, among the employees of the selected company. The study is an attempt to build a clearer understanding of the characteristics of sustainable leadership and how it contributes to transformation and change in the business organization.
Keywords: Responsible leadership; Sustainability; Corporate social responsibility; Sustainable leadership